TESTING NEW EPISTEMOLOGICAL BREAK PHYSICAL EDUCATION (Fiep Bulletin - online, 2013)
This article discusses the evolution of the methods of physical education as a dichotomy between science and education and health also presents a discussion of the current paradigm of Physical Education, with an emphasis on motor skills. Therefore, we investigated the following question:What were the changes of physical education facing the construction of knowledge beyond the human machine?This study was conducted from a qualitative approach has been developed through a literature review with a brief history of the methods and objectives of physical education.With the completion of the survey, it was observed that the concept of education psychomotor can be reviewed with the study of human movement in order to identify these possible developments of Physical Education in motion with intentionality and consciousness. Thus, understood as the Physical Education Science of Human Kinetics, includes humans and their diversity, from their strengths and needs.
Keywords: Trends in Physical Education; Kinetics; Physical Education.